If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -12 = -6 + 3y Solving -12 = -6 + 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. -12 + -3y = -6 + 3y + -3y Combine like terms: 3y + -3y = 0 -12 + -3y = -6 + 0 -12 + -3y = -6 Add '12' to each side of the equation. -12 + 12 + -3y = -6 + 12 Combine like terms: -12 + 12 = 0 0 + -3y = -6 + 12 -3y = -6 + 12 Combine like terms: -6 + 12 = 6 -3y = 6 Divide each side by '-3'. y = -2 Simplifying y = -2
| 5/7=3/x | | -10k=20(1-10k)-20 | | -13m-16=36 | | x^7+9x^7= | | 2(16-7p)=-23-9p | | -6p-6=-36 | | 8=vf-3 | | 25=5(7x)-3 | | 15(y+3)=6(y-5) | | X^2-3x-40=o | | 10(v+2)-4v=3(2v+3)-15 | | ((8/4)6)x2 | | 5a-75=-20(a+20) | | p-2=5 | | -14x+1=-55 | | 10x+40=4x-8 | | 13x-12=4(3x+4)-4 | | -45+X=-27 | | -13=k-13+14k | | 5m-5=-25 | | x-.20x=338 | | 10x+40=4x+8 | | 45+X=-27 | | 8+10k-11k=0 | | x-.20x=512 | | (-30(-17))-(210(-3))= | | -36=-11n+8n | | 6y-60=42 | | 12=x-(-11) | | -36=k-13+14k | | 13p+6=32 | | sin^-1(3.2/4) |